The Prevalence of Traumatic Brain Injury Among Young Offenders in Custody: A Systematic Review. Issue 2 (March 2015) - Hughes, Nathan; Williams, W. H.; Chitsabesan, Prathiba; Walesby, Rebecca C.; Mounce, Luke T. A.; Clasby, Betony
Abstract : Objectives: To examine the prevalence of traumatic brain injury (TBI) among young people in custody and to compare this with estimates within the general youth population. Design: Systematic review of research from various national contexts. Included studies were assessed for the relevance of the definition of TBI and the research population, and the quality of the study design. Results: Ten studies were identified for inclusion in the review. Four of these studies included control groups. No studies examining comorbidity of TBI and other neurodevelopmental disorders among incarcerated young people were identified. Conclusion: Reported prevalence rates of brain injury among incarcerated youth range from 16.5% to 72.1%, with a rate of 100% reported among a sample of young people sentenced to death. This suggests considerable levels of need among incarcerated young people. Where control groups or directly comparable studies within the general population exist, there is strong and consistent evidence of a prevalence of TBI among incarcerated youth that is substantially greater than that in the general population. This disparity is seemingly more pronounced as the severity of the injury increases.